Comparative transcriptomics revealed neurodevelopmental impairments and ferroptosis induced by extremely small iron oxide nanoparticles - Lyu, Zhaojie; Kou, Yao; Fu, Yao; Xie, Yuxuan; Yang, Bo; Zhu, Hongjie; Tian, Jing (Frontiers in Genetics, 2024)
Iron oxide nanoparticles are a type of nanomaterial composed of iron oxide (Fe3O4 or Fe2O3) and have a wide range of applications in magnetic resonance imaging. Compared to iron oxide nanoparticles, extremely small iron oxide nanoparticles (ESIONPs) (~3 nm in diameter) can improve the imaging performance due to a smaller size. However, there are currently no reports on the potential toxic effects of ESIONPs on the human body. In this study, we applied ESIONPs to a zebrafish model and performed weighted gene co-expression network analysis (WGCNA) on differentially expressed genes (DEGs) in zebrafish embryos of 48 hpf, 72 hpf, 96 hpf, and 120 hpf using RNA-seq technology. The key hub genes related to neurotoxicity and ferroptosis were identified, and further experiments also demonstrated that ESIONPs impaired the neuronal and muscle development of zebrafish, and induced ferroptosis, leading to oxidative stress, cell apoptosis, and inflammatory response. Here, for the first time, we analyzed the potential toxic effects of ESIONPs through WGCNA. Our studies indicate that ESIONPs might have neurotoxicity and could induce ferroptosis, while abnormal accumulation of iron ions might increase the risk of early degenerative neurological diseases.